Controllable Unidirectional Emission With Double-Resonant Plasmonic Antenna - Fei Liu; Shengyin Ye; Kailiang Zhang; Guangjun Ren (IEEE Photonics Journal, 2017)
A double-resonant metal–insulator–metal (MIM) optical antenna is theoretically proposed to control the emission directivity of a dipolar emitter. The nanoantenna consists of an in-plane side-by-side assembling metallic nanobar dimer on the top and a metallic nanoplate on the bottom, separated by a dielectric spacer. Unidirectional and enhanced emission of the emitter is wavelength dependent. It is controllable by changing the phase differences of constituting elements of the antenna, induced by the double magnetic resonances at different wavelengths. The results can be potentially used in near-field sample detection, solar cell, and single-photon source.